Correlation between the autonomic nervous system and neoplastic disease - Zygulska, Aneta Lidia; Furgala, Agata; Krzemieniecki, Krzysztof (European Journal of Oncology and Environmental Health, 2018)
The physiological role of the autonomic nervous system (ANS) includes maintenance of homeostasis and response to stressors. Sympathetic nervous system (SNS) is involved at early stages of tumorigenesis via β-adrenergic signaling and via central and local norepinephrine/epinephrine release from SNS nerve fibers. Parasympathetic nervous system (PNS) promotes invasion and dissemination of cancers using cholinergic receptors. In this paper, we review published evidence regarding the impact of SNS and PNS on solid tumor development, and discuss the importance of those findings for clinic and prevention.